Primary Cardiac Hemangioendothelioma in an Infant: A Case Report - Jeong-wook Seo; Mi Kyoung Song; Sung-hye Park; Hye Eun Park; Sin Ae Park (The Korean Society of Pediatric Hematology-Oncology, 2019)
Primary cardiac tumors are rare, with a prevalence of 0.001-0.2%. Among such tumors, cardiac hemangioendotheliomas are some of the most uncommon. In Korea, there have been no reports of hemangioendothelioma occurring in the heart of infants. We herein report a case of an infant that was admitted to our medical center and presented with cough and a runny nose. The initial diagnosis was acute bronchiolitis. Cardiomegaly was observed on chest radiography. Echocardiography revealed a tumor measuring 3.5×4.0 cm in the right atrium. The infant was transferred to a tertiary medical center for tumor excision. The excised lesion was 3.8×3×3.2 cm in size, and biopsy confirmed a diagnosis of hemangioendothelioma. In this case report, we describe our experience with a rare case involving cardiac tumor in an infant with an upper respiratory tract infection.